Designing Inclusive Islamic-Based Humanistic Multicultural Education: Strategy and Implementation - Fiddini, Muktazzah (Yayasan Dinamika Ilmu Banyuwangi, 2025)
This study aims to examine in depth the concept, strategies, challenges, and implementation of inclusive Islamic value-based multicultural education through a literature review approach. Multicultural education is an urgent need in a pluralistic society like Indonesia, which consists of various ethnicities, religions, cultures, and languages. Inclusive Islamic values such as tolerance (tasamuh), justice ('adl), brotherhood (ukhuwwah), and rahmatan lil 'alamin are believed to be able to provide a strong foundation in realizing education that respects differences. Through a review of various literature sources, this study found that effective multicultural education strategies include the integration of inclusive values in the curriculum, teacher training, and the development of an open and dialogical school culture. The main challenges in its implementation include ideological resistance, intergroup stereotypes, and a lack of critical awareness in educational institutions. Therefore, a joint commitment is needed from the government, educators, and society to make multicultural education a key pillar in forming a tolerant and just generation.